If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 1) = x + -4 Reorder the terms: 2(1 + x) = x + -4 (1 * 2 + x * 2) = x + -4 (2 + 2x) = x + -4 Reorder the terms: 2 + 2x = -4 + x Solving 2 + 2x = -4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2 + 2x + -1x = -4 + x + -1x Combine like terms: 2x + -1x = 1x 2 + 1x = -4 + x + -1x Combine like terms: x + -1x = 0 2 + 1x = -4 + 0 2 + 1x = -4 Add '-2' to each side of the equation. 2 + -2 + 1x = -4 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = -4 + -2 1x = -4 + -2 Combine like terms: -4 + -2 = -6 1x = -6 Divide each side by '1'. x = -6 Simplifying x = -6
| 2x(x-5)=10 | | -8x^2-26x+15=0 | | 0.9x-3.2=0.4 | | (x-2)+(x+6)=9 | | a^2-18a-80=0 | | 7a-(a+7)= | | f(x)=4-3 | | X-7.8=-5.7 | | 3a+(4-2a)= | | 5ln(3x)=10 | | 62.92*.544= | | -3z-11=8-3z | | 68=(2x+2y) | | -3(t-1)+6t=8t-6 | | 7x+4-9x=12-19x+17x-8 | | 3p-q=-12 | | 3x-4-7x=2x-4+2x | | a+(2a+3)= | | 68=2x+2y | | 4(y-6)=-15y | | f(x)=-2-7 | | (2x+1)(x+4)+13=2x-10x | | 4x+90=14x+10 | | 425=-250+15y | | 7x+4-9x= | | 8m-15+2m=23+10m-2 | | (2x+1)(x+4)13=2x-10x | | 2(2-1)+3(3-1)= | | 1-8b=1-5b | | 75+37=x | | -2x-5y=-4 | | 4(y-9)=-20 |